THE USAGE OF MICROWAVE TECHNIQUE TO DESTROY POTATO SAMPLES IN ORDER TO DETERMINE HEAVY METALS BY ATOMIC ABSORPTION SPECTROFOTOMETRY - B. Rajković, M.; D. Sredović, I.; R. Milojković, S.; V. Tošković, D.; D. Stanojević, D. (Journal of Engineering & Processing Management, 2011)
Preparation of samples by microwave technique consists of large number of phases, from taking samples till receiving homogeneous solution for instrumental analysis. Samples preparation can include combination of drying, wetting, extraction, digestion, analytic separation and solvent removing. The analysis of content of heavy metals in potato from Braničevo Region by the usage of atomic absorption spectrophotometry (AAS) showed that certain samples of potato contain more than 1ppm of lead, and that certain samples contain amount of lead which is even 4 times higher than allowed MDK value. As for cadmium, all samples contains amount which is 7 to even 20 times higher than allowed MDK value. Chrome and nickel are not allowed by Law to be in products for human diet, and by this analysis it is determined that these samples contain chrome (total). In none of these samples was determined the presence of nickel. Received results of the analysis showed that large amounts of chemical (mineral) fertilizers were used at these soils. According to received results it can be concluded that the soil as well as increased usage of phosphate fertilizers are main cause for the presence of heavy metals in potato.